Comprehensive Family Caregiver Support and Caregiver Well-Being: Preliminary Evidence From a Pre-post-survey Study With a Non-equivalent Control Group - Smith, Valerie A.; Lindquist, Jennifer; Miller, Katherine E. M.; Shepherd-Banigan, Megan; Olsen, Maren; Campbell-Kotler, Margaret; Henius, Jennifer; Kabat, Margaret; Van Houtven, Courtney Harold (Frontiers in Public Health, 2019)
Introduction: In May 2010, the Caregivers and Veterans Omnibus Health Services Act of 2010, was signed into law in the United States, establishing the Program of Comprehensive Assistance for Family Caregivers (PCAFC) provided through the VA Caregiver Support Program (CSP). Prior to this program, over half of family caregivers reported being untrained for the tasks they needed to provide. The training through PCAFC represents the largest effort to train family caregivers in the U.S., and the features of the program, specifically a monthly stipend to caregivers and access to a Caregiver Support Coordinator at each VA medical center nationally, make it the most comprehensive caregiver support program ever enacted in the U.S. Methods: The purpose of this study is to examine the association between PCAFC participation and caregiver well-being following enrollment, comparing participating PCAFC caregivers to caregivers who applied to but were not approved for PCAFC participation (non-participants). Well-being is defined using three diverse but related outcomes: depressive symptoms, perceived financial strain, and perceived quality of the Veteran’s health care. Additional well-being measures also examined include the Zarit Burden Inventory and positive aspects of caregiving. Results: The survey sample comprised of 92 caregivers approved for PCAFC and 66 caregivers not approved. The mean age of responding caregivers was 45; over 90% of caregivers were female; and over 80% of caregivers were married in both groups. We find promising trends in well-being associated with PCAFC participation. First, the perception of financial strain declined among participants compared to non-participants. Second, while depressive symptoms did not improve for the PCAFC caregivers, depressive symptoms increased among non-participants. Third, perceived quality of the Veteran’s VA healthcare was no different between participants and non-participants. However, the 158 returned surveys reflect only a 5% response rate; hence this evidence is preliminary. Conclusion: Despite cautioning that results be interpreted as preliminary, this study provides unique descriptive information about young caregivers of U.S. post-9/11 Veterans, and offers a first step in filling the evidence gap about how comprehensive caregiver support in the U.S. may affect caregiver well-being. These preliminary findings should be explored and validated in a larger sample.